The effectiveness of oral anti-SARS-CoV-2 agents in non-hospitalized COVID-19 patients with nonalcoholic fatty liver disease: a retrospective study - Yang, Chun-Chi; Tsai, Ya-Wen; Wang, Su-Hung; Wu, Jheng-Yan; Liu, Ting-Hui; Hsu, Wan-Hsuan; Huang, Po-Yu; Chuang, Min-Hsiang; Sheu, Ming-Jen; Lai, Chih-Cheng (Frontiers in Pharmacology, 2024)
Background: The effectiveness of the novel oral antiviral agents, nirmatrelvir plus ritonavir and molnupiravir, in treating COVID-19 in patients with nonalcoholic fatty liver disease is unclear. Objective: To assess the effectiveness of novel oral antiviral agents against COVID-19 among patients with nonalcoholic fatty liver diseases. Methods: This retrospective cohort study used the TriNetX Research Network to identify non-hospitalized patients with COVID-19 and nonalcoholic fatty liver disease between January 1, 2022, and June 30, 2023. Propensity score matching was used to form two matched cohorts treated with or without nirmatrelvir-ritonavir or molnupiravir. Results: In the two matched cohorts of 6,358 patients each, the use of novel oral antiviral agents was associated with a significantly lower risk of all-cause emergency department visits, hospitalization, or mortality (6.59% versus 8.24%; hazard ratio [HR], 0.80; 95% confidence interval [CI], 0.70–0.91). The novel antiviral group had a significantly lower risk of all-cause emergency department visits (HR, 0.85; 95% CI, 0.74–0.99). Additionally, the incidence of hospitalization was significantly lower in the oral antiviral group than in the control group (HR, 0.71; 95% CI, 0.55–0.90). There were no deaths in the oral antiviral group but 12 deaths in the control group. Conclusions: Novel oral antiviral agents are beneficial for treating COVID-19 in patients with nonalcoholic fatty liver disease.